Commenter Galien et Hippocrate à la Renaissance ou comment Brasavola met à mal le régime grec - Pietrobelli, Antoine (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2010)
This paper aims to draw attention on a commentary written by the famous Antonio Musa Brasavola upon the Galenic Commentary on Regimen in Acute Diseases. Published in 1546 by this disciple of Leoniceno and Manardi, this work is a very brilliant illustration of the Ferrara’s medical Hellenism. Returning to Galenic and Hippocratic Greek texts, Brasavola shows a huge classical scholarship in his interpretation. But surprisingly for a follower of the Hellenists, Brasavola mentions also many Arabic writers to make them converse with Greek authorities. Confronting the medical tradition of the past with his own experience as a practitioner, Brasavola seems to cast doubt on some aspects of the Greek regimen in acute diseases, opening the way to significant changes in the theories of digestion and fever.